2019
DOI: 10.1111/jgh.14749
|View full text |Cite
|
Sign up to set email alerts
|

Balloons larger than 15 mm can increase the risk of adverse events following endoscopic papillary large balloon dilation

Abstract: Background and Aim Although endoscopic papillary large balloon dilation (EPLBD) has been widely used to facilitate the removal of difficult common bile duct stones, however, the outcomes have not yet been investigated in terms of the diameter of the balloon used. We aimed to compare the clinical outcomes between EPLBD using smaller (12–15 mm, S‐EPLBD) and larger balloons (> 15 mm, L‐EPLBD). Methods Six hundred seventy‐two patients who underwent EPLBD with or without endoscopic sphincterotomy for common bile du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In a Korean study analyzing 672 papillary/biliary large balloon dilation for difficult stones, perforations and fatal complications occurred only in patients dilated from >15 to 20 mm. No perforation was observed in patients dilated from 12 to 15 mm [16] and in our technique, we never dilate >15 mm. The presence of a stone could increase the risk of perforation, but this was not observed in our study as well as in the one by Park et al [9] and 2 other case reports [7, 8].…”
Section: Discussionmentioning
confidence: 82%
“…In a Korean study analyzing 672 papillary/biliary large balloon dilation for difficult stones, perforations and fatal complications occurred only in patients dilated from >15 to 20 mm. No perforation was observed in patients dilated from 12 to 15 mm [16] and in our technique, we never dilate >15 mm. The presence of a stone could increase the risk of perforation, but this was not observed in our study as well as in the one by Park et al [9] and 2 other case reports [7, 8].…”
Section: Discussionmentioning
confidence: 82%
“…In a Korean study analyzing 672 EBLBD for difficult stones, perforations and fatal complications only occurred in patients dilated > 15-20 mm. No perforation was observed in patients dilated 12-15 mm[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings revealed that overdilation is not a significant factor associated with perforation. Furthermore, several prior studies that performed overdilation revealed that overdilation is not a risk factor for adverse events [7,12,16] and that fatal perforation cases without overdilation have occurred when using a balloon > 15 mm [17]. This may be due to the fact that, unlike pigs, humans have SP.…”
Section: Discussionmentioning
confidence: 99%